Isotopic and elemental profiles of Mediterranean buffalo milk and cheese and authentication of Mozzarella di Bufala Campana PDO: An initial exploratory study. (1st July 2019) - Bontempo, Luana; Barbero, Alice; Bertoldi, Daniela; Camin, Federica; Larcher, Roberto; Perini, Matteo; Sepulcri, Angela; Zicarelli, Luigi; Piasentier, Edi
Highlights: Stable isotope ratio and elemental analysis characterise Mozzarella di Bufala Campana (MBC). Differences were found between MBC and relative milk. Geographical origin have effect on the elemental and isotopic fingerprint of MBC. Stable isotope ratios and elements are effective to distinguish PDO and non-PDO mozzarella. Abstract: Mozzarella di Bufala Campana (MBC) is a PDO cheese produced from whole buffalo milk in specific regions of southern Italy. Due to the high price and the limited amount of buffalo milk, MBC is potentially subject to mislabelling. Stable isotope ratio analysis combined with elemental analysis is one powerful technique for detecting the authenticity of PDO cheeses. Here, the elemental and isotopic profiles of authentic samples of buffalo milk and the corresponding MBC samples collected in the reference area in winter and summer are presented in an initial exploratory study. By merging MBC-PDO samples with non-PDO samples of buffalo mozzarella produced both inside and outside the reference area, a model was developed to classify product categories for this cheese. Despite the differences occurring during processing, along with differences in the season and production area, the model was effective in distinguishing PDO and non-PDO mozzarella, particularly when non-PDO cheeses were made outside the MBC reference area.